An alternative inoculation technique of Colletotrichum gloeosporioides on mango for early anthracnose tolerance screening - Monteon Ojeda, Abraham (2018)
The importance of having a technique that allows an efficient expression of symptoms of anthracnose is based on the early differentiation of cultivars and the optimization of genetic, material and financial resources. The objective of this research was to generate an alternative inoculation technique for Colletotrichum gloeosporioides on mango for early anthracnose tolerance screening. On this technique was optimized some of the most relevant components such as isolate virulence, conidial density, the inoculum deposition on leaves and using of surfactants. The study was carried in Iguala, Mexico, during the production cycles 2015-2016. C. gloeosporioides was biologically and culturally characterized. Gro and Sin monosporic strains were isolated from leaves, flowers, fruits and branches with anthracnose symptoms from commercial mango orchards located in Guerrero and Sinaloa states, Mexico. These strains show mycelial growth at 2.2 and 2.1 cm of diameter per day, spore density of 4.3x106, 3.9x106 conidia/ml, germination of 27 and 26%, virulence, with incubation period 4.5 and 4.1 days after inoculation, incidence of 90 and 92% and severity of 3.2 and 3.5 cm of diameter. The highest incidence and severity values with the lowest incubation period, was obtained using Gro isolate (1x105 conidia/ml) and polyoxyethylene-20-sorbitan monolaurate as spreader-sticker inoculated on the abaxial surface on detached young leaves, 15-20 days old, with a soft brush and incubated under dark condition. This inoculation technique allowed the optimal expression of C. gloeosporioides virulence in mango leaves and could be incorporated as a tool in the early differentiation of tolerance and susceptibility among cultivars.